In vivo Protein Interference: Oral Administration of Recombinant Yeast-Mediated Partial Leptin Reduction for Obesity Control - Yue, Feng; Du, Lihong; Wang, Ruyu; Han, Baoquan; Zhang, Xiaojun; Yao, Zhangzhang; Zhang, Wenqiang; Cai, Chang; Zhang, Zhiying; Xu, Kun (Frontiers in Microbiology, 2022)
Obesity related diseases are always the major health problems covering the world. Serial studies have reported that obesity development is closely related to the out-of-control of leptin encoded by obesity gene (ob). The latest report declaimed ‘Less Is More’, a model that partial leptin reduction triggers leptin sensitization and contributes to obesity control. Here, we came up with a novel concept, in vivo protein interference (iPRTi), an interesting protein knock-down strategy for in vivo partial leptin reduction. Firstly, specific immune response against leptin induced by the oral administration of ob recombinant yeast was confirmed. Subsequentially, leptin resistance was observed in diet-inducing obese (DIOing) mice and oral administration with ob recombinant yeast declined the circulating leptin and reduced significantly the body weight gain. To further investigate whether the iPRTi strategy is capable for obesity management, the diet-induced obese (DIOed) mice were administrated with ob recombinant yeast. All the indexes examined including the circulating leptin, triglyceride, and total cholesterol, as well as food intake and weight gain, demonstrated a positive effect of the iPRTi strategy on obesity control. In short, this study provides a novel strategy for the potential application of recombinant yeast for the therapy of obese individuals with leptin resistance.